Giant multipole resonances - Khvastunov, V.M. (Вопросы атомной науки и техники, 2003)
The review of the experimental discovery of and further research into giant multipole resonances performed at the Kharkov Institute of Physics and Technology is outlined. These results are compared with theoretical and experimental ones obtained in other laboratories.